2020
DOI: 10.1149/1945-7111/aba3ff
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Electrochemical Exfoliation and Chemical Functionalization of Graphene for Supercapacitor Electrodes

Abstract: The demand for efficient electrochemical energy storage technology, such as supercapacitors, continues to increase as both the energy and power demands of devices grow. Graphene has attracted wide interest in addressing this energy challenge due to its high conductivity and specific surface area. However, in reality the hydrophobic properties and the restacking of the graphene sheets during device manufacture leads to significantly lower storage performance than that theoretically predicted for isolated sheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…In particular, covalent modification of graphene has been found to be able to control the surface chemistry, porosity, and surface roughness and remains stable under operating conditions . For example, functionalizing graphene with aryl diazonium salts improved the graphene’s dispersibility significantly in aprotic solvent and aqueous solution. , Additionally, supercapacitor electrodes produced from the functionalized graphene possessed a specific capacitance of at least five times higher than the unfunctionalized graphene electrodes due to the redox reactions caused by the functional groups and less restacking. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, covalent modification of graphene has been found to be able to control the surface chemistry, porosity, and surface roughness and remains stable under operating conditions . For example, functionalizing graphene with aryl diazonium salts improved the graphene’s dispersibility significantly in aprotic solvent and aqueous solution. , Additionally, supercapacitor electrodes produced from the functionalized graphene possessed a specific capacitance of at least five times higher than the unfunctionalized graphene electrodes due to the redox reactions caused by the functional groups and less restacking. , …”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, galvanostatic charge/discharge (GCD) measurements have shown that graphene functionalized with 4-nitrobenzenediazonium (NBD) for 30 min exhibited the best electrochemical properties followed by graphene functionalized with 4-bromobenzenediazonium (BBD) for 60 min compared to pristine graphene . The synergistic effect of combining fct-graphene and 1T-MoS 2 greatly enhanced the electrochemical behavior of the coin cells which manifest excellent cyclability (90% capacitance retention after 10 000 cycles) and exceptional capacitance (290 F cm –3 at 0.5 A g –1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the presence of fluorophenylene moieties allowed to increase the interlayer distance and provide better transport properties for electrolyte ions. The combination of the two factors offers an enhanced capacitance in comparison with more traditional modification methods utilizing diazonium chemistry [47][48][49].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…10,11 There are various preparation methods of 2D-graphene such as exfoliation and cleavage, chemical vapor deposition (CVD), thermal decomposition, laser-based reduction, chemical, and electrochemical reduction. [12][13][14][15][16][17][18][19][20][21][22] Among them, solution-based reduction of graphene oxide (GO) is a commonly used attractive method for its easy operation in recent years. 8,22,23 Chemically modified graphene (reduced graphene oxide; rGO) are attractive precursors for inexpensiveness and can be applied for producing large scale with a high yield.…”
mentioning
confidence: 99%